Microwave assisted extraction of betacyanin from peel of red dragon fruit (Hylocereus polyrhizus) (Study of the extraction time and the ratio of materials : solvent) - Widya Rahmawaty Saman; Arie Febriyanto Mulyadi; Susinggih Wijana (Fakultas Pertanian Universitas Ichsan Gorontalo, 2023)
This study aims to get the right combination and determine the best treatment effect of extraction time and the ratio of solvents to the yield and quality of the skin pigment red dragon fruit using MAE (Microwave Assisted Extraction) with 100 watts of power. In the collection phase, the pigment betacyanin used the method of randomized block design with 2 factors, namely the time of extraction (T) consisting of 3 levels (T1, T2, and T3 respectively - each 5, 10, and 15 minutes) and the second factor is the ratio of materials: Solvent (R) consisting of 2 levels (R1 and R2) each - each 1:20 and 1:30 (w/v). Each treatment was repeated 3 times to obtain 18 units of the experiment. Followed by DMRT (Duncan Multiple Range Test) if there is an interaction between the two factors or further test BNT. From the research that has been done, the best treatment is obtained by the old extraction treatment of 5 minutes and the ratio of materials: solvent 1:30 (w/v) with a temperature range of ± 60°C produces the best characteristics with a total value betacyanin 0.4120mg/100g, 2.25 pH value, the total yield of as much as 15.11%, the level of brightness (L*) 20.4, the intensity of the red color (a*) 10.8, and the intensity of the yellow color (b*) 6.5.